IgG2a monoclonal antibodies inhibit human tumor growth through interaction with effector cells. - Herlyn, D (1982)
Monoclonal antibodies of IgG2a isotype specifically inhibited growth of human tumors in nude mice. Twenty-three monoclonal antibodies of other isotypes showed no tumoricidal reactivity. Complement depletion of nude mice had no effect on tumor suppression by monoclonal antibody. The role of T and killer cells as mediators of the monoclonal antibody effect in nude mice was virtually excluded. On the other hand, macrophages were strongly incriminated as effector cells because silica treatment of nude mice abolished the tumoricidal effect of monoclonal antibody. IgG2a monoclonal antibody-dependent macrophage-mediated cytotoxicity assays with human tumor cells in culture resulted in specific lysis of tumor cells.